2021
DOI: 10.1111/adj.12817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of artificial tooth position in dentures fabricated by heat curing and additive manufacturing

Abstract: Background: The purpose of this study was to compare the displacement of tooth arrangement in dentures fabricated by additive manufacturing (AM) and heat curing. Methods: Three-dimensional (3D) scanning was performed for edentulous jaw models. After the teeth were arranged, 3D scanning for the wax denture was performed. Heat-cured dentures were fabricated with heat-cure polymer resin. Based on data obtained by subtracting the model data from wax denture data, AM dentures were fabricated from ultravioletcured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This inference was shared by the studies by Awada et al [9] and Homaei et al [11] that we selected for our review, which showed the use of ceramic in the fabrication of prostheses using CAD/CAM technology. It is quite remarkable that all the inferences that we observed after reviewing the studies that we selected for our review [9][10][11][12][13][14][15][16][17][18][19][20][21][22] are in agreement with investigations done by Papadiochou et al [30], Ahmed et al [31], and Bilgin et al [32]. An inference that these three studies shared is that by improving the quality of the instruments and systems utilized, CAD/CAM in several dental specialties has opened up new potential for providing high-quality dental care while also theoretically increasing patient convenience [30][31][32].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This inference was shared by the studies by Awada et al [9] and Homaei et al [11] that we selected for our review, which showed the use of ceramic in the fabrication of prostheses using CAD/CAM technology. It is quite remarkable that all the inferences that we observed after reviewing the studies that we selected for our review [9][10][11][12][13][14][15][16][17][18][19][20][21][22] are in agreement with investigations done by Papadiochou et al [30], Ahmed et al [31], and Bilgin et al [32]. An inference that these three studies shared is that by improving the quality of the instruments and systems utilized, CAD/CAM in several dental specialties has opened up new potential for providing high-quality dental care while also theoretically increasing patient convenience [30][31][32].…”
Section: Discussionmentioning
confidence: 92%
“…Again, CAD/CAM deserves praise. Due to the fact that it is invisible, the lingual bracket procedure is highly common [ 19 ]. The wires and bracket systems for the lingual bracket system are produced using CAD/CAM fabrication [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…Similar results were found when printed denture teeth position was compared to conventional mandibular dentures, but the authors interestingly reported a significant difference in position on maxillary dentures. 47 One in vitro study compared the accuracy and trueness of different denture teeth polymers printed with different printers. 48 As expected, significant differences were observed amongst the combinations of printer and material.…”
Section: Complete Removable Dental Prosthesesmentioning
confidence: 99%